EFFECTIVELY USING ARCHITECTURAL TERMS THROUGH COMPARING THEIR DEFINITIONS IN PRACTICAL LESSONS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article describes most used architectural words with specialized texts. Researchon technical vocabulary has shown a significant underestimation of the role played by technical vocabulary in specialized texts and lack of information about how technical vocabulary relates to other types of vocabulary. Also in this article has showna study of the technical vocabulary in an architecture text and the technical vocabulary in an applied linguistics texts. This articlereports on the significance information for language learners and ESP teachers.